2019
DOI: 10.1128/aac.01545-18
|View full text |Cite
|
Sign up to set email alerts
|

Rutin Attenuates Vancomycin-Induced Nephrotoxicity by Ameliorating Oxidative Stress, Apoptosis, and Inflammation in Rats

Abstract: Nephrotoxicity is the major limiting factor for the clinical use of vancomycin (VCM) for treatment of serious infections caused by multiresistant Gram-positive bacteria. This study investigated the renal protective activity of rutin in a rat model of VCM-induced kidney injury in male Wistar rats. VCM administered intraperitoneally at 200 mg/kg twice daily for 7 successive days resulted in significant elevation of blood urea nitrogen and creatinine, as well as urinary N-acetyl-β-D-glucosaminidase. Coadministrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 52 publications
4
29
0
Order By: Relevance
“…42 Rutin ameliorates carbon tetrachloride or vancomycininduced kidney injury in mice models. 44,45 In the present study, levels of intracellular ROS could be reduced by rutin in BisGMA-treated macrophages. AOEs are capable of the deactivation and detoxification of ROS.…”
Section: Effects Of Rutin On Bisgma-inhibited Aoe Activities In Rawsupporting
confidence: 54%
“…42 Rutin ameliorates carbon tetrachloride or vancomycininduced kidney injury in mice models. 44,45 In the present study, levels of intracellular ROS could be reduced by rutin in BisGMA-treated macrophages. AOEs are capable of the deactivation and detoxification of ROS.…”
Section: Effects Of Rutin On Bisgma-inhibited Aoe Activities In Rawsupporting
confidence: 54%
“…These studies have been reviewed in detail 111 . Since then, spirulina and pycnogenol , 112 mitoTEMPO, naringenin, 113 a free radical scavenger zingerone, 114, 115 DHA‐enriched phosphatidylcholine (DHA‐PC), 116 rutin, 117 and silymarin 118 have been evaluated in animal studies. In our opinion, the antioxidants that are most ready for clinical trials include preparations that are already clinically available, such as atorvastatin, vitamin C, vitamin E, N‐acetylcysteine, erythropoietin, and erdosteine.…”
Section: Potential Strategies For Preventionmentioning
confidence: 99%
“…This result suggested a possible role of rutin in diminishing the signal generated either via integral membrane death receptor proteins or via mitochondrial cytochrome c release pathway, and finally reducing the activation of effector caspase-3, thereby attenuating the apoptotic death and disruption concerning renal tubular cells induced by cisplatin [21]. In addition, rutin supplementation attenuated significantly vancomycin-induced renal apoptosis through decreasing the activity of caspase-3 and caspase-9 [39]. Moreover, Ma et al [36] reported that different doses of rutin supplementation decreased the release of cytochrome c and the activity of caspase-3 in kidneys of CCl4treated mouse.…”
Section: : Effect Of Rutin (R) On Nuclear Factor Kappa B (Nf-bmentioning
confidence: 91%
“…NF-B is a necessary transcriptional mediator for production of the proinflammatory cytokines that plays a pivotal role in the injury of tubular epithelial cells through generating ROS [38]. Qu et al [39] established that a protecting effect of rutin on vancomycin-caused renal damage was through reducing the NF-B expression and TNF-α generation to the control levels. In addition, rutin alleviated cisplatininduced renal injury through its inhibitory effect on NF-B and TNF-α pathway mediated inflammation [21].…”
Section: : Effect Of Rutin (R) On Nuclear Factor Kappa B (Nf-bmentioning
confidence: 99%